Increased prevalence of femoroacetabular impingement on the elderly with fractures of the proximal femur - Busato, Thiago Sampaio (SICOT J, 2021)
Objectives: Femoroacetabular impingement (FAI) has been recently related to several pathologies, besides chondral injury and hip arthritis. We aim to investigate the prevalence of FAI morphology in an elderly cohort hospitalized due to a proximal femur fracture and compare these findings to a control group. We hypothesize that limited medial rotation due to FAI’s morphology could increase stresses to the proximal femur, acting as a facilitating mechanism for fractures in this region. Therefore, a higher prevalence of FAI morphology would be present in the study group. Methods: A retrospective cross-sectional study was performed based on the analysis of radiographic images in AP and lateral views of the fractured hip. Firstly, we have set to measure FAI prevalence in an elderly cohort victimized by fractures of the proximal by measures of the alpha, Tönnis, and lateral center edge angles of a hundred consecutive patients hospitalized for proximal femur fractures. Secondly, we have analyzed the possible relationship between the FAI subtypes and the type of fracture. Finally, we have compared this sample’s data with that of a similar control cohort not affected by fracture. Results: The cohort in this study displayed a higher prevalence of pathological changes in the Tönnis, center-edge, and alpha angles with odds ratios of 3.41, 2.56, and 4.80, respectively (with statistical significance). There was also a significant relationship between cam-type FAI and intertrochanteric fractures, corroborating our initial hypotheses. Conclusions: This study demonstrated that a cohort of older patients affected by fractures of the proximal femur had an increased prevalence of radiographic signs of femoroacetabular impingement. Furthermore, this is the first study demonstrating a statistically significant relationship of cam-type FAI with intertrochanteric fractures, suggesting a possible cause and effect relationship.